Analysis of potential market segments for new hybrid forage seeds in East Africa - Junca Paredes, John Jairo; Florez, Jesus Fernando; Enciso, Karen; Hernández Mahecha, Luis Miguel; Triana Ángel, Natalia; Burkart, Stefan (2024)
Low productivity and quality of pastures together with a hostile environmental setting limit the development of livestock farming in East Africa. As an alternative to these challenges, new hybrid forage seeds adapted to environmental and productive conditions are being developed by CIAT together with its strategic partner, Grupo Papalotla. Accordingly, the objective of this study is to estimate the size and value of the potential market for the hybrids under development, namely interspecific Urochloa and Megathyrsus maximus hybrids. Based on livestock herd sizes, geographic profiling studies, and expected yield assumptions, the potential hectares for these two materials are estimated. The market value is then calculated according to the commercial prices of hybrid forages or similar materials in the current market. The study was applied to countries in East Africa, where the main dairy producers of the continent are located. According to the results, the market of interspecific Urochloa hybrids has a size of 352,158 ha and an annual value of US$ 62,479,997. In this case, Ethiopia, Tanzania, and Kenya hold a combined market share of 83%. The potential market of Megathyrsus maximus hybrids is 494,471 ha with a value of US$ 94,648,595. Here, South Sudan, Ethiopia, and Tanzania hold a market share of 71.63%. This stresses that there are significant possibilities for the development of a market for improved forage seeds. However, it is necessary to create the right conditions for the adoption of such new materials. Access to the market on competitive terms together with constant extension services are key elements in this regard.